2015
DOI: 10.1186/s12947-015-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac masses by real-time perfusion imaging echocardiography

Abstract: BackgroundDiagnosis of cardiac masses is still challenging by echocardiography and distinguishing tumors from thrombi has important therapeutical implications. We sought to determine the diagnostic value of real-time perfusion echocardiography (RTPE) for cardiac masses characterization.MethodsWe prospectively studied 86 patients, 23 with malignant tumors (MT), 26 with benign tumors (BT), 33 with thrombi and 6 with pseudotumors who underwent RTPE. Mass perfusion was analyzed qualitatively and blood flow volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…Nevertheless, the great limitation of TTE resides in its inability to distinguish between thrombi and benign or malignant tumors. 5 The diagnostic accuracy of TTE depends on the experience of the sonographer and the image quality. This study found that CEUS provides more information to improve the effectiveness of ultrasound diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the great limitation of TTE resides in its inability to distinguish between thrombi and benign or malignant tumors. 5 The diagnostic accuracy of TTE depends on the experience of the sonographer and the image quality. This study found that CEUS provides more information to improve the effectiveness of ultrasound diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…It can provide important information about a mass, including its size, location, boundaries, and blood flow. Contrast echocardiography also helps to differentiate cardiac masses . Computed tomography or magnetic resonance imaging may help in further characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast echocardiography also helps to differentiate cardiac masses. 7 Computed tomography or magnetic resonance imaging may help in further characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time perfusion contrast echocardiography can evaluate the vascular pattern of the mass, where the pectinate muscle and tumor show vascularity but thrombi are either avascular or have very low vascularity but this technique has low sensitivity. [ 3 ] The presence of a septic vegetation at the mouth of LAA had been reported that gave an exact picture of floating mass. [ 4 ] LAA is difficult to image by echo from the transthoracic approach, and the TEE has a greater sensitivity and high-negative predictive value for detecting mass in LAA specially thrombus.…”
mentioning
confidence: 99%